2017
DOI: 10.1038/micronano.2017.22
|View full text |Cite
|
Sign up to set email alerts
|

Toward point-of-care management of chronic respiratory conditions: Electrochemical sensing of nitrite content in exhaled breath condensate using reduced graphene oxide

Abstract: We present a portable non-invasive approach for measuring indicators of inflammation and oxidative stress in the respiratory tract by quantifying a biomarker in exhaled breath condensate (EBC). We discuss the fabrication and characterization of a miniaturized electrochemical sensor for detecting nitrite content in EBC using reduced graphene oxide. The nitrite content in EBC has been demonstrated to be a promising biomarker of inflammation in the respiratory tract, particularly in asthma. We utilized the unique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(32 citation statements)
references
References 57 publications
(63 reference statements)
1
29
0
Order By: Relevance
“…Ions dissolved in aqueous media play a fundamental role in plants, animals, and humans. Ions regulate the biological processes at the single cell scale, enable the propagation of electronic signals and maintain a suitable balance between the fluids of the extracellular and intracellular environments, which is extremely important for several processes including nerve impulses, hydration, muscle function, and the regulation of pH level 1 – 7 . The in situ quantification of the ion concentration in aqueous media is thus gaining significant interest in several emerging fields including biomedical diagnostics, environmental monitoring, healthcare products, water and food test and control, agriculture industry and security 8 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Ions dissolved in aqueous media play a fundamental role in plants, animals, and humans. Ions regulate the biological processes at the single cell scale, enable the propagation of electronic signals and maintain a suitable balance between the fluids of the extracellular and intracellular environments, which is extremely important for several processes including nerve impulses, hydration, muscle function, and the regulation of pH level 1 – 7 . The in situ quantification of the ion concentration in aqueous media is thus gaining significant interest in several emerging fields including biomedical diagnostics, environmental monitoring, healthcare products, water and food test and control, agriculture industry and security 8 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Taniselass et al [134] focused on the applications of graphenebased (bio)sensors in medicine, not only for detecting cancer cells but also for monitoring non-communicable diseases (NCDs). The authors highlighted many studies on GO-or rGObased devices for detecting different markers for cardiovascular problems, [176] lung cancer, [177] asthma, [178] and diabetes [179] and revealed that the combination and functionalization of GO and rGO could result in versatile, sensitive, and specific devices for monitoring NCDs. Recently, Hu et al [180] described a highly sensitive sensor for quantifying α-synuclein, a protein that mutates or is present at high levels in Parkinson's disease (PD) patients.…”
Section: Clinical Diagnosis Applicationsmentioning
confidence: 99%
“…There's an urgent need for improved, minimally invasive methods for the diagnosis and monitoring of respiratory diseases. For example, the scientists in Rutgers University-New Brunswick have created a graphene-based sensor that could lead to the earlier detection of looming asthma attacks and improve the diagnosis of asthma and other respiratory diseases, preventing hospitalizations and deaths [66]. It is followed by E05-U05C (Nanofilm), A12-V01 (Medicines, pharmaceuticals), B05-C06 (Elemental C or S), and D05-H09 (Testing and detection (Except Bacteria, Fungi, Viruses)).…”
Section: Patent Hotspots and Frontsmentioning
confidence: 99%